EMPLOYEE WELL-BEING AND ADAPTIVE PERFORMANCE IN HYBRID MSMES: CONNECTING WORK DESIGN, PSYCHOLOGICAL SAFETY, AND MANAGERIAL SUPPORT - Diah Fatma Sjoraida; Anggun Yolistina (Organisasi Kreatif Indonesia Emas, 2025)
This conceptual and integrative review develops a framework for employee well-being in hybrid MSMEs in micro, small, and medium enterprises. It addresses the problem that hybrid work can widen flexibility while also producing role ambiguity, digital fatigue, uneven access to support, and fragmented social connection in small organizations. Drawing on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, and resilience, the paper explains how role and workload clarity, psychological safety, inclusive communication, managerial support, well-being feedback routines can be organized as mutually reinforcing routines. The proposed pathway moves from problem diagnosis and capability mapping to bounded experimentation, evidence review, resource reconfiguration, and learning retention. No primary survey, interview, experimental, administrative, or statistical data are claimed. The framework links these mechanisms to employee well-being, adaptive performance, team cohesion, retention, organizational resilience and identifies managerial, institutional, and research implications suitable for resource-constrained enterprises.